IMPLEMENTASI MEDIA SMART HOUSE MENGGUNAKAN PENDEKATAN CRT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV - Elva Brigesti, Jacinda; Yuniawatika; Lilyana Abiba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the lack of learning media in the Pancasila Education subject on ethnicity material. Therefore, the researcher created an interactive learning media innovation to improve students' interest and learning outcomes. The purpose of this study is to improve learning outcomes by implementing the Smart House media for fourth grade students of SD Laboratorium UM Malang City. In the Smart House media there are materials and various important information about the diversity of ethnicities in Indonesia. The method in this study used Classroom Action Research (CAR) which was carried out in 2 cycles. The subjects of this study were 27 fourth grade students of SD Laboratorium UM. Data collection tools included class observation sheets, interviews, and essay questions about ethnicity which could be used to determine the improvement in student learning outcomes. In cycle I of 27 students, 22 students (81%) achieved learning completion, while 5 students (19%) had not completed it. In cycle II, all 27 fourth grade Bilingual students achieved learning completion with a percentage (100%). So it can be concluded that the use of Smart House media with the Culturally Responsive Teaching (CRT) approach can improve the learning outcomes of fourth grade Bilingual students at SD Laboratorium UM Malang City.